2020
DOI: 10.1155/2020/5204917
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of Abelmoschus manihot on Type 2 Diabetic Nonproliferative Retinopathy and the Involvement of VEGF

Abstract: Objective. To evaluate the efficacy of Abelmoschus manihot in treating type 2 diabetic nonproliferative retinopathy. Methods. It was a randomized controlled clinical trial. The recruited eighty subjects with type 2 diabetic nonproliferative retinopathy were randomly divided into treatment group and control group. The two groups received basic treatments including control of blood glucose, blood pressure and blood lipid, management of diet, exercise and health education, and monitoring of relevant indicators. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Our previous study has proven that Abelmoschus manihot could improve DR severity, ETDRS vision, macular edema, and serum VEGF levels in type 2 diabetes (7). Hyperoside is a primary active ingredient of Abelmoschus manihot (29), and the hyperoside content level in Abelmoschus manihot is notably higher compared with other herbal medicines (30).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our previous study has proven that Abelmoschus manihot could improve DR severity, ETDRS vision, macular edema, and serum VEGF levels in type 2 diabetes (7). Hyperoside is a primary active ingredient of Abelmoschus manihot (29), and the hyperoside content level in Abelmoschus manihot is notably higher compared with other herbal medicines (30).…”
Section: Discussionmentioning
confidence: 97%
“…The recent clinical study of our team indicated that Abelmoschus manihot could improve the severity of DR, ETDRS vision scores and macular edema in type 2 diabetes, and the speci c therapeutic mechanism seemed to be associated with inhibited vascular endothelial growth factor (VEGF) levels, which needed further investigations (7). Previous studies have showed that the activation of transforming growth factor-beta 1 (TGF-β1)/micro-RNA 200b (miR-200b)/VEGF pathway by high glucose might play an essential role in the destruction of blood-retinal barrier (BRB) and the pathogenesis of DR (8-10).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the principal treatment technique for neovascular eye illnesses is the inhibition of VEGF activity. Zingiber zerumbet (L.) ERK1/2 and NF-κB [121] Dendrobium chrysotoxum Lindl Protein kinase C and NF-κB [122] Polygonum cuspidatum High-mobility group box-1 (HMGB1) [123] Salvia miltiorrhiza (Lamiaceae) Ang-II-induced NADPH oxidase-4 (Nox4) [124] Lycium barbarum (Solanaceae) Caspase-3, PPAR- [125] Astragalus membranaceus (Fabaceae) ERK1/2, NFkB, VEGF [126,127] Ginkgo biloba HIF-1α and VEGF [128] Puerariae lobata (Fabaceae) AGEs, VEGF [129] Vaccinium myrtillus VEGF/VEGFR2 [130] Lonicerae japonicae Flos VEGF/VEGFR2 [131] Abelmoschus Manihot VEGF/VEGFR2 [132] Fructus Arctii VEGF/VEGFR2 [133] RAS/VEGF pathway: The angiotensin with its receptor complex energizes the expression of VEGF during ONV by activating NF-kB.…”
Section: Retinoprotective Drugsmentioning
confidence: 99%